2020
DOI: 10.1038/s41598-020-65124-8
|View full text |Cite
|
Sign up to set email alerts
|

Silicon tackles butachlor toxicity in rice seedlings by regulating anatomical characteristics, ascorbate-glutathione cycle, proline metabolism and levels of nutrients

Abstract: Reckless use of herbicides like butachlor (Buta) in the fields represents a serious threat to crop plants, and hence to their productivity. Silicon (Si) is well known for its implication in the alleviation of the effects of abiotic stresses; however, its role in mitigating Buta toxicity is not yet known. Therefore, this study was carried out to explore the role of Si (10 µM) in regulating Buta (4 µM) toxicity in rice seedlings. Buta reduced growth and photosynthesis, altered nitric oxide (NO) level and leaf an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Thus, although several reports state that Si application can boost Pro levels to increase the antioxidant efficiency [ 82 ], the findings reported herein confirm the hypothetical role of Pro as a stress signal, rather than as a tolerance mechanism against herbicide exposure. Similarly, Tripathi et al [ 59 ], Spormann et al [ 11 ] and Sousa et al [ 83 ] found that pesticide- and Zn-mediated increases in Pro levels were efficiently counteracted by the application of Si, salicylic acid, and brassinosteroids (24-epibrassinolide), respectively. Thus, it appears that Si and nano-SiO 2 ’s ameliorative effects on ROS homeostasis and LP in shoots are not related to the action of Pro, but rather to other antioxidant components.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus, although several reports state that Si application can boost Pro levels to increase the antioxidant efficiency [ 82 ], the findings reported herein confirm the hypothetical role of Pro as a stress signal, rather than as a tolerance mechanism against herbicide exposure. Similarly, Tripathi et al [ 59 ], Spormann et al [ 11 ] and Sousa et al [ 83 ] found that pesticide- and Zn-mediated increases in Pro levels were efficiently counteracted by the application of Si, salicylic acid, and brassinosteroids (24-epibrassinolide), respectively. Thus, it appears that Si and nano-SiO 2 ’s ameliorative effects on ROS homeostasis and LP in shoots are not related to the action of Pro, but rather to other antioxidant components.…”
Section: Discussionmentioning
confidence: 98%
“…Not only did plants show a better growth potential at the macroscopic level, the results concerning biomass production and organ elongation further confirmed this trend. Curiously, the only available record exploring the ameliorative features of Si nutrition against herbicide toxicity was recently published [ 59 ]. In agreement with our data, Tripathi et al [ 59 ] also observed a positive effect of Si, provided as 10 µM sodium silicate, when 25-day-old rice plants were exposed to butachlor (4 µM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Butachlor has a significant effect on weed control, but it can also decrease the amount of very-long-chain fatty acids in the plasma membrane of crop seedlings and lead to plant cell death. 5 For example, butachlor is highly toxic to algae which are beneficial to the growth of rice plants, such as the N 2 -fixing cyanobacterium Nostoc muscorum . 6,7 On the other hand, butachlor enters environmental water from the soil, and has a significant impact on the ecological environment and food safety.…”
Section: Introductionmentioning
confidence: 99%